Short- and long-term impacts of the COVID-19 epidemic on urban PM2.5 variations: Evidence from a megacity, Chengdu. (1st February 2023) - Jin, Qian; Luo, Yina; Meng, Xiangrui; Feng, Miao; Huang, Chengmin
Abstract: As the new coronavirus pandemic enters its third year, its long-term impact on the urban environment cannot be ignored, especially in megacities with more than millions of people. Here, we analyzed the changes in the concentration levels, emission sources, temporal variations and holiday effects of ambient fine particulate matter (PM2.5 ) and its chemical components in the pre- and post-epidemic eras based on high-resolution, long time-series datasets of PM2.5 and its chemical components in Chengdu. In the post-epidemic era, the PM2.5 concentration in Chengdu decreased by 7.4%, with the components of PM2.5 decreasing to varying degrees. The positive matrix factorization (PMF) results indicated that the emissions from soil dust and industrial production were significantly lower during the COVID-19 lockdown period and post-epidemic era than those in the pre-epidemic era. In contrast, the contribution of secondary aerosols to PM2.5 during these two periods increased by 2.7% and 6.6%, respectively. Notably, we found that PM2.5 and its components substantially decreased on workdays and holidays in the post-epidemic era due to the reduced traffic volume and outdoor activities. This provides direct evidence that changes in the habitual behavior patterns of urban residents in the post-epidemic era could exert an evident positive impact on the urban environment. However, the higher PM2.5 concentration was observed due to the increased consumption of regular (As4 S4, Xionghuang in Chinese) and "sulfur incense" during the Dragon Boat Festival holiday in the post-epidemic era. Finally, we examined the potential effects of sporadic COVID-19 outbreaks on the PM2.5 concentration in Chengdu, and there was no decrease in PM2.5 during two local COVID-19 outbreak events due to the strong influence of secondary pollution processes. Highlights: Long-term impacts of the COVID-19 epidemic on urban PM2.5 were analyzed. Emissions from transportation and industry reduced in the post-epidemic era. PM2.5 concentration significantly dropped over workdays and holidays in the post-epidemic era. PM2.5 concentration conversely increased during the Dragon Boat Festival in the post-epidemic era.